2008
DOI: 10.1016/j.jss.2007.12.758
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-Stimulated RAW 264.7 Macrophage Inducible Nitric Oxide Synthase and Nitric Oxide Production Is Decreased by an Omega-3 Fatty Acid Lipid Emulsion

Abstract: Background-Omega-3 FA (ω-3 FA) have been demonstrated to have anti-inflammatory properties; postulated to occur through several principal mechanisms, including 1) displacement of arachidonic acid from the cellular membrane, 2) shifting of PGE 2 and LTB 4 production and 3) molecular level alterations including decreased activation of NF-κB and AP-1. An additional regulator that is likely associated is the production of nitric oxide (NO) by nitric oxide synthetase. NO is a short-lived free radical involved in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 22 publications
(6 reference statements)
2
48
0
3
Order By: Relevance
“…In contrast, the saturated fatty acid palmitic acid, also detected in walnut extract, was shown stimulate TLR4 signaling pathways [23]. Other studies have demonstrated that LA and oleic acid do not affect NO production [24], but will inhibit the stimulatory effects of saturated fatty acids [23] and LPS [25] in macrophages. Since individual fatty acids in walnut extract have been reported to exert opposing effects on TLR4-mediated signaling, the impact of the combination of fatty acids in walnut extract on microglial activation was difficult to predict.…”
Section: Discussionmentioning
confidence: 93%
“…In contrast, the saturated fatty acid palmitic acid, also detected in walnut extract, was shown stimulate TLR4 signaling pathways [23]. Other studies have demonstrated that LA and oleic acid do not affect NO production [24], but will inhibit the stimulatory effects of saturated fatty acids [23] and LPS [25] in macrophages. Since individual fatty acids in walnut extract have been reported to exert opposing effects on TLR4-mediated signaling, the impact of the combination of fatty acids in walnut extract on microglial activation was difficult to predict.…”
Section: Discussionmentioning
confidence: 93%
“…Subsequently, 2 h after treatment with lysoPCs (0-20 μM), the formation of NO, TNF-α, and IL-6 in cells was stimulated by including LPS (1 μg/ml), followed by further incubation at 37°C for around 20 h. Finally, the NO level in cell-free media was determined using Griess assay [32,33], and the levels of TNF-α as well as IL-6 were measured by ELISA kit [34] according to the manufacturers' manuals.…”
Section: Preventive Effect Of 2-docosahexaenoyl-lysopc On Lps-inducedmentioning
confidence: 99%
“…Polyunsaturated fatty acids (PUFAs) of the n-6 and n-3 series, especially arachidonic acid (20:4n-6, ARA), eicosapentaenoic acid (20:5n-3, EPA) and docosahexaenoic acid (22:6n-3, DHA), are considered as the precursors for the synthesis of eicosanoids, regulators of cell signaling and gene expression and the most powerful modulators of cell membrane fluidity (Calder, 2006;Yaqoob and Calder, 2007). In mammals, alteration in PUFAs contents of the immune cells was demonstrated to be associated with the alteration of phagocytic capacity (Kew et al, 2003), nitric oxide (NO) production (Aldridge et al, 2008;Ambrozova et al, 2010;, inflammatory cytokine production (Yan et al, 2013) as well as antigen presentation capability (Calder, 2008). These immune-modulatory effects of dietary fatty acids also occurred in farmed fish (Li et al, 2013a;Montero et al, 2010;Xu et al, 2010;Zuo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%